COMPOSITION AND ANTIBACTERIAL ACTIVITIES OF ETHYL ACETATE EXTRACTS FROM 3 SPECIES OF LAURENCIA (RHODOPHYTA) - Hy, Le Ho Khanh; Hanh, Nguyen Kim; Ky, Pham Xuan; Ha, Dao Viet; Hong, Nguyen Thu; Anh, Nguyen Phuong (Vietnam Journal of Marine Science and Technology, 2018)
This paper is concerned with composition and antibacterial activities of ethyl acetate extracts from 3 species of Laurencia (Rhodophyta): Laurencia papillosa, Laurencia flexilis and Laurencia cartilaginea collected from the southern coasts of Vietnam. The results showed that ethyl acetate (EtOAc) extracts of these species displayed antibacterial activities against Salmonella typhimurium, Escherichia coli and Bacillus subtilis. The qualitative investigations revealed the presence of two sesquiterpene secondary metabolites Elatol and Palisadin A in EtOAc extracts from the three above- mentioned Laurencia species.